Quantifying Tradeoffs for Marine Viruses - Record, Nicholas R.; Talmy, David; Våge, Selina (Frontiers in Marine Science, 2016)
The effects of viruses on marine microbial communities are myriad. The high biodiversity of viruses and their complex interactions with diverse hosts makes it a challenge to link modeling work with experimental work. In various trophic groups, trait-based approaches have helped to simplify this complexity, as traits describe organism properties in terms of taxon-transcending units, allowing for easier identification of generic, underlying principles. By predicting large-scale biogeography of different plankton functional types based on key sets of traits and their associated tradeoffs, these approaches have made major contributions to our understanding of global biogeochemistry and ecology. This review addresses the question of how a trait-based approach can make contributions toward understanding marine virus ecology. We review and synthesize current knowledge on virus traits with a focus on quantifying the associated tradeoffs. We use three case studies--virulence, host range, and cost of resistance--to illustrate how quantification of tradeoffs can help to explain observed patterns, generate hypotheses, and improve our theoretical understanding of virus ecology. Using a nutrient-susceptible-infected-virus model as a framework, we discuss tradeoffs as a link between model building (theory) and experimental design (practice). Finally, we address how insights from virus ecology can contribute back to the trait-based ecology community.